An equilibrium model of the electricity market considering the participation of virtual power plants. (November 2022) - Dai, Xinyun; Chen, Haoyong; He, Qianya
Abstract: Led by the carbon peak and neutrality targets, there is a consensus for renewable energy to compete in the electricity market alongside conventional energy sources. Based on co-evolutionary algorithms, this paper proposes an equilibrium model of electricity market with the participation of virtual power plants composed of wind farms and distributed energy storage. The model constructs a secondary clearing mechanism with the aim of promoting hydropower consumption and simulates the game behavior of various players in a market environment from the perspective of power producers. A co-evolutionary algorithm is used to solve the market equilibrium point for the game model, and the optimal fitness function is used to judge whether the generator's strategy combination is optimal. The simulation results validate the effectiveness of the market model and the co-evolutionary algorithm. The results show that the secondary clearance mechanism is effective in increasing the rate of wind power consumption and improving the overall welfare of society.